PENERAPAN TEKNOLOGI INJECTOR CLEANER UNTUK PENINGKATAN KUALITAS LAYANAN JASA SERVIS DI KIKI MOTOR MENUJU BENGKEL PROFESIONAL - Nanang Romandoni; Muhammad Taali; Kholis Nur Faizin; Farid Majedi; Indah Puspitasari; Abdul Aziz (JURNAL ABDIMAS DOSMA (JAD), 2022)
The development of technology in the automotive sector, especially motorcycles is increasing. This is indicated by the use of Electronic Fuel Injection (EFI) technology for the inclusion of the fuel system. Therefore, motorcycle repair shops must continue to upgrade their mechanical skills and expertise to meet customer needs in vehicle servicing. Kiki Motor Workshop is a motorcycle repair shop that is engaged in the service and replacement of motorcycle spare parts on micro exhibits. Judging from the service activities in the workshop, the average category of motorcycle being serviced is conventional technology (carburetor). Efforts are needed to improve the quality of human resources so that the workshop is able to receive motorcycle service services with EFI technology. The application of injector cleaner technology is a community service program that aims to improve the quality of services at the Kiki Motor workshop. In addition to improving the quality of the workshop, this program is expected to increase the income of the workshop.